Adverse events following vaccination in the French armed forces: An overview of surveillance conducted from 2002 to 2010 - Mayet, A; Haus-Cheymol, R; Bouaiti, E A; Decam, C; Simon, F; Mérens, A; Spiegel, A; Meynard, J B; Deparis, X; Migliani, R (Euro surveillance : bulletin européen sur les maladies transmissibles, 2012)
French military personnel are subject to a compulsory vaccination schedule. The aim of this study was to describe vaccine adverse events (VAE) reported from 2002 to 2010 in armed forces. VAE are routinely surveyed by the military Centre for epidemiology and public health. For each case, military practitioners fill a notification form, providing patient characteristics, clinical information and vaccines administered. For this study, VAE following influenza A(H1N1)pdm09 vaccination were excluded. Among the 473 cases retained, 442 (93%) corresponded to non-severe VAE,including local, regional and systemic events, while 31 corresponded to severe VAE, with two leading to significant disability. The global VAE reporting rate (RR) was 14.0 per 100,000 injections. While stationary from 2002 to 2008, the RR increased from 2009. The most important observations were a marked increase of VAE attributed to Bacillus Calmette-Guérin (BCG) vaccine from 2005 to 2008, a high RR observed with the inactivated diphtheria-tetanus (toxoids)-poliovirus vaccine combined with acellular pertussis vaccine (dTap-IPV) from 2008 and an increase in RR for seasonal influenza vaccine VAE in 2009. Our RR for severe VAE (1.1 VAEper 100,000) appears comparable with rates observed among United States civilians and military personnel. The increase observed from 2009 could be partly explained by the influenza A(H1N1)pdm09 pandemic which increased practitioner awareness towards VAE. In conclusion, the tolerance of the vaccines used in French armed forces appears acceptable.